Ultimate compressive strength of stiffened panel: An empirical formulation for flat-bar type - Kim, D.K. (MDPI AG, 2020)
This research aims to study the ultimate limit state (ULS) behaviour of stiffened panel under longitudinal compression by a non-linear finite element method (NLFEM). There are different types of stiffeners mainly being used in shipbuilding, i.e., T-bar, flat-bar, and angle-bar. However, this research focuses on the ultimate compressive strength behaviour of flat-bar stiffened panel. A total of 420 reliable scenarios of flat-bar stiffened panel were selected for numerical simulation by the ANSYS NLFEM. The ultimate strength behaviours obtained were used as data for the development of closed form shape empirical formulation. Recently, our group proposed an advanced empirical formulation for T-bar stiffened panel, and the applicability of the proposed formulation to flat-bar stiffened panel is confirmed by this study. The accuracy of the empirical formulation obtained for flat-bar stiffened panel was validated by finite element (FE) simulation results of statistical analysis (R2 = 0.9435). The outcome obtained will be useful for ship structural designers in predicting the ultimate strength performance of flat-bar type stiffened panel under longitudinal compression. Â© 2020 by the authors.